Planejamento urbano e competência da União: a contribuição dos planos urbanísticos da União para o desenvolvimento urbano - Silva, Carlos Eduardo (2012)
The existence of national and regional urban planning to guide the use and occupation of land has become fundamental in a country such as Brazil with its continental proportions and great diversity of environments, culture and social and economic conditions. The lack of national urban planning is seen in the unarticulated promotion of Union investment policies in public works in a particular region of the country, or even in incentives for the installation of companies and economic activities, that end up impacting on the infrastructure and development of the municipalities. The lack of a national policy on territorial organization and urban development can also be seen when looking at the elaboration and execution of numerous sectorial policies that have territorial impacts and seeing how uncoordinated they are and how they lead to superimposed actions by different Federal organs. For this reason, the 1988 Constitution provides the Union with the role of coordinating national and regional development plans that have direct impact on land territory. As well as this, the national and regional plans for land organization and social and economic development are set out by judicial ordering as an instrument of urban policy. In this sense, the Union plays a fundamental part in the implementation of a system of structural plans, since territorial plans within its ambit allow for the establishment of the integration of a variety of plans, actions and investments in infrastructure and development among the different levels of government, providing greater efficiency in administrative action. This way, the lack of plans within the Federal ambit could imply in the Union suffering a ruling of delayed action (by means of a direct lawsuit on the grounds of unconstitutionality for reasons of omission) as well as repercussions in the area of civil responsibility and in the actual control of the legality of activities that have significant consequences within the ambit of land ownership in a context of absolute lack of planning